Second to Fourth Digit Ratio (2D:4D) in Hypertension Disease - Servi, Refik; Akkoc, Ramazan Fazil; Aksu, Feyza; Cetin, Seda; Kavakli, Ahmet; Ogeturk, Murat (Wiley, 2025)
Objectives The second to fourth digit ratio (2D:4D) is a sexually dimorphic trait thought to reflect prenatal exposure to sex hormones. 2D:4D has been proposed as a potential biomarker for various adult diseases, and evidence suggests that it may also predict cardiovascular disease risk. This study aimed to ascertain the 2D:4D of both hands in patients with hypertension and to determine whether there were any differences between this ratio and that of a control group. Methods The study was carried out on 400 subjects with a hypertension diagnosis, 200 males and 200 females, and the same number of 400 healthy subjects. 2D:4D was calculated by measuring the lengths of both hands' second and fourth fingers for males and females. The height, weight, and mean body mass index were also calculated for the hypertension and control groups. Results The mean BMI was significantly higher in the hypertension group, in the overweight category, whereas it was in the normal weight category in the control group (p < 0.001). The 2D:4D was significantly higher in both males and females with hypertension compared to controls. In males, the 2D:4D was elevated in both the right and left hands in the hypertension group compared to controls (p = 0.001). A similar trend was observed in females, with significantly higher 2D:4D in both hands in the hypertension group (p < 0.001). Conclusion The 2D:4D may be regarded as a significant factor in determining a person's risk of hypertension from birth, allowing those in the risk group to lead more preventive lives.
Keywords: 2D:4D; anthropometry; digit ratio; hypertension